Engenharia metabólica de Bacillus subtilis para produção de biossurfactante - Zocca, Vitória Fernanda Bertolazzi [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
---
Metabolic engineering of Bacillus subtilis for biosurfactant production
Keywords: CRISPR-Cas9; Biologia Sintética; Surfactina; Biossurfactante; Bacillus subtilis; Synthetic Biology; Surfactin; Biosurfactant